Party realignment and single-issue voters - Christian Cox; Ian Shapiro (PLoS ONE, 2025)
This paper studies the effect of a single-issue referendum on political party realignment. We consider the Conservative Party in the United Kingdom in the aftermath of a referendum on the British exit from the European Union. We look at the change in positions of Conservative Members of Parliament using a novel dataset tracking their opinions on British membership of the EU and their election outcomes between 2015 and 2022. Our findings show that MPs who resisted switching to a pro-Leave position faced significantly higher electoral losses. We then consider various models of switching, showing that safe seats are strong predictors. These results highlight the sensitivity of political parties to single-issue politics, underscoring how such environments can contribute to broader populist movements in modern democracies.